Kadar Air dan Warna Penyedap Alami Jamur Tiram (Pleurotus Ostreatus) Berdasarkan Perlakuan Awal (Pre-treatment) - Nadhifah, Ainun; Kholifatuddin, Yunan; Handarsari, Erma (Universitas Muhammadiyah Semarang, 2021)
Flavoring seasonings are food additives added with the aim of increasing flavor (palatability) and covering up deficiencies in food in terms of taste. The natural glutamate content of mushrooms has the potential to be used as a flavoring ingredient, one of which is oyster mushrooms. The quality of natural flavoring of oyster mushrooms is determined by the formula of the ingredients and the way they are produced. The drying process can affect the water content and color of seasoning.This study aims to determine the water content and natural flavoring of oyster mushrooms based on initial treatment. This study was an experimental study using a Completely Randomized Design with 6 treatment trials (non-blanching, blanching, sodium bisulfite immersion, citric acid immersion, blanching + sodium bisulfite immersion, and blanching + citric acid immersion), and 3 test replications. The moisture content test was performed by the AOAC oven method and color analysis was measured using Konica Minolta CR-10 Color Reader. Observational data were analyzed using univariate analysis.The results showed that the initial treatment had a tendency to increase water content. Moisture content for all samples based on pretreatment meets the quality criteria for dry products that is 10%. The results of the color analysis showed an increase in the value of each treatment but did not show any real difference in color. The treatment using sodium bisulfite immersion and blanching showed an increase in brightness intensity and a good chroma value category compared to the control value. Based on OHue value in each treatment has the same color scheme, namely yellow – red.Keywords: Oyster mushroom, Water Content, Color, Pre treatment, blanching